2020
DOI: 10.1515/edu-2020-0100
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Its Impact on Academic and Social Life of Undergraduate University Students in Ghana: A Structural Equation Modeling Approach

Abstract: AbstractStress is concomitant with students’ life and can have a significant impact on their lives, and even how they go about their academic work. Globally, in every five visits by patients to the doctor, three are stress-related problems. This study examined stress and its impact on the academic and social life among students of a university in Ghana. The descriptive cross-sectional survey design was employed. Using the stratified and simple random (random numbers) sampling m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
0
10
0
3
Order By: Relevance
“…Findings from that study and the current study indicate comparable proportions of students experiencing moderate stress (63.2% in the previous study vs. 69.8% in the current study). Other studies of Ghanaian undergraduate students that used the PSS-10 reported that 70% of first-year educational psychology students ( Amponsah and Owolabi, 2011 ), 93% of undergraduate students were moderately stressed ( Edjah et al, 2020 ), and 59% of nursing students were moderately or highly stressed ( Bam et al, 2014 ). While stress levels appear to vary somewhat based on the student population's course of study, these findings suggest that, for many higher education students across the world, including Ghana, university life is at least moderately stressful.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from that study and the current study indicate comparable proportions of students experiencing moderate stress (63.2% in the previous study vs. 69.8% in the current study). Other studies of Ghanaian undergraduate students that used the PSS-10 reported that 70% of first-year educational psychology students ( Amponsah and Owolabi, 2011 ), 93% of undergraduate students were moderately stressed ( Edjah et al, 2020 ), and 59% of nursing students were moderately or highly stressed ( Bam et al, 2014 ). While stress levels appear to vary somewhat based on the student population's course of study, these findings suggest that, for many higher education students across the world, including Ghana, university life is at least moderately stressful.…”
Section: Discussionmentioning
confidence: 99%
“…While we maintain that most studies exploring university student stress and health outcomes fail to include sub-Saharan African students, there are notable exceptions ( Amponsah and Owolabi, 2011 ; Auerbach et al, 2016 ; Bam et al, 2014 ; Edjah et al, 2020 ; Kamulegeya et al, 2020 ; Misigo, 2015 ) where information that included Kenyan, Nigerian, Ugandan, and Ghanaian students has been published. Studies referring to Ghanaian students have been cited throughout this discussion section, but in terms of non-Ghanaian studies, in Kenya, female students reported higher stress, but a different survey instrument was used ( Misigo, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eshun (1999) suggested that Ghanaian students possess a strong kinship and good social support which buffers them from maladaptive functioning. While the above studies document adaptive psychological outcomes for Ghanaian students, other studies provide evidence for significant levels of stress and other difficulties (Edjah et al, 2020). In fact, comparative, cross-cultural studies may mask the within-culture stressors unique to university students in Ghana.…”
Section: Psychological Well-being Among Ghanaian University Studentsmentioning
confidence: 95%
“…Academic activities in various educational institutions are fertile grounds for breeding stress among teachers and students (Edjah et al, 2020;Adom et al, 2020a). In its aggravated form, stress turns into burnout (Shailesh, 2018).…”
Section: Introductionmentioning
confidence: 99%